The biochemistry of archaea (archaebacteria) - Kates, Morris; Kushner, Donn; Matheson, A. T. (New comprehensive biochemistry ;, 1993)
This volume brings together recent knowledge concerning the three major groups of archaea: extreme halophiles, extreme thermophiles and methanogens. It includes coverage of: general metabolism, bioenergetics, molecular biology and genetics, and evolutionary relations.